Verification of Model Transformations to Refactoring Mobile Social Networks - Asztalos, Mark; Ekler, Péter; Lengyel, László; Levendovszky, Tihamér (Electronic Communications of the EASST, 2011)
Verification of model processing programs, where only the definitions of the program and the languages of the models to be transformed are analyzed, has become a fundamental issue in model-based software engineering. This analysis may become very complex, but it is performed only once and the results are independent from concrete input models. The formal background of verification methods for graph rewriting-based model transformations has become a subject of research recently. In previous work, we have provided fundamental formal and algorithmic background of a (semi-)automated verification approach for graph transformations. This work concludes these components and put them together to introduce the implementation of a verification system fully integrated into a model transformation framework, VMTS. The strong points of our approach is its usability, its implementation in an existing tool, and its extendibility, which are demonstrated on a case study in the application domain of mobile centric social networks. Our results show that the verification of graph rewriting-based model transformations can be largely automated.